2014
DOI: 10.4102/koedoe.v56i2.1160
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of guided versus non-guided interpretation in the Kruger National Park, South Africa

Abstract: In the face of growing pressure placed on the natural environment, the study on which this article is based considered the effectiveness of interpretive provision in mitigating the harmful effects of tourism on the environment. The aim of this research was to determine whether guided or non-guided interpretation is most effective in reaching the stated goals of interpretation. The four key goals of interpretation, namely visitor satisfaction, knowledge gain, attitude change and modification of behaviour intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…Further investigation of these websites and other discussions of interpretation reveal considerable consensus about how interpretation makes a difference and what it makes a difference to. The core functions or benefits of interpretation can be organised by level of conceptualisation from the individual visitor to improving sustainability beyond the destination (Roberts et al, 2014). At the level of the individual visitor, interpretation is claimed to be an important part of the visitor experience contributing to making a visit meaningful, interesting and rewarding or enjoyable (Interpretation Australia, 2014;Moscardo, 2013).…”
Section: Interpretation: Definitions and Functions In Tourismmentioning
confidence: 99%
“…Further investigation of these websites and other discussions of interpretation reveal considerable consensus about how interpretation makes a difference and what it makes a difference to. The core functions or benefits of interpretation can be organised by level of conceptualisation from the individual visitor to improving sustainability beyond the destination (Roberts et al, 2014). At the level of the individual visitor, interpretation is claimed to be an important part of the visitor experience contributing to making a visit meaningful, interesting and rewarding or enjoyable (Interpretation Australia, 2014;Moscardo, 2013).…”
Section: Interpretation: Definitions and Functions In Tourismmentioning
confidence: 99%
“…One potential solution is a combination of information sources (Coghlan and Kim, 2012) and methods considered more eff ective, such as new technologies (Wolf, Stricker and Hagenloh, 2013) and guided tours. However, the motivation of visits also plays an important role in these cases (Poudel and Nyaupane, 2013), and the diff erences between these alternatives and standard interpretive trails might not be noticeable (Roberts, Mearns and Edwards, 2014). Th e previous results indicate statistically signifi cant diff erences in knowledge and information among all three groups.…”
Section: Environmental Knowledgementioning
confidence: 58%
“…Similarly, visitors' actual knowledge at the Walpole-Nornalup National Park, Australia also showed no differences before and after they were exposed to the newly installed interpretive signs in the park (Hughes & Morrison Saunders, 2002). Roberts et al (2014) study at the Kruger National Park, South Africa also found no differences in the knowledge between visitors who took guided and non-guided interpretation. In Kinabalu Park, very few research related to interpretation were undertaken (Jacobson, 2009;Bidder et al 2016).…”
Section: Evaluation Of Interpretationmentioning
confidence: 89%
“…Several studies on the evaluation of interpretation had been carried out in the context of Malaysian natural environment (Mohd Hafizal Ismail, 2008;Jacobson, 2009;Roslina, Manohar, Ismail Adnan, Azlizam, & Mohd Aswad, 2013;Amin, Chan, & Mohd Shukri, 2014;Lim, Manohar, Azlizam, & Zakaria, 2016;Bidder et al, 2016). Majority of the studies yielded either partially positive or positive findings (Tubb, 2003;Madin & Fenton, 2004;Powell & Ham, 2008;Roslina et al, 2013) but there have also been studies that reported very little or no differences at all in the visitors' knowledge before and after they were exposed to interpretation (Papageorgiou, 2001;Hughes & Morrison-Saunders, 2002;Novey & Hall, 2006;Roberts, Mearns, & Edwards, 2014). Tubb (2003) study at the High Moorland Visitor Centre in Dartmoor National Park, United Kingdom found that visitors' knowledge and awareness increased after they were exposed to the interpretation at the centre.…”
Section: Evaluation Of Interpretationmentioning
confidence: 99%